Design for developing an electronic student worksheet based on organic food plant cultivation - Anjarwati, Sulis; Sari, Alvina Putri Purnama (Jurnal Mangifera Edu, 2024)
The importance of teaching staff in innovating in the era of the Industrial Revolution 4.0 is something that must be considered, one of which is innovating in presenting teaching materials. Electronic-based teaching materials that can be easily used by students are electronic-based student worksheets (E-LKM). E-LKM represents an easily assessable resource for a student. The utilization of E-LKM by students should be in alignment with their specific needs, one of which is the role of universities in promoting the cultivation of organic food crops. Therefore, one of the steps forward involves designing an E-LKM based on the cultivation of organic food plants. This research introduces a novel approach, which will develop an E-LKM based on organic food crop cultivation which is expected to provide insight to students about the importance of cultivating organic food crops as a form of food self-sufficiency. The development of this E-LKM design based on organic food crop cultivation adapts the ADDIE development model. It can be concluded that the ADDIE Model is used in the design of developing E-LKM based on organic food crop cultivation because it has systematic steps, is presented in detail, and produces specific products. From our result, evaluation criteria encompass material validity, practicality, and readability aiming for a minimum score of 85.0-100%.